Regional extracorporeal membrane oxygenation retrieval service during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic: an interdisciplinary team approach to maintain service provision despite increased demand. (23rd September 2020) - Rafiq, Muhammad U; Valchanov, Kamen; Vuylsteke, Alain; Taghavi, Fouad J; Iyer, Swetha B; Sudarshan, Catherine D; Fowles, Jo-Anne; Anderson, Simon; Govender, Pooveshni; Holmes, Miranda; White, Alexander; Mishra, Abhi; et al.
Abstract: OBJECTIVES: Coronavirus disease 2019 is a new contagious disease that has spread rapidly across the world. It is associated with high mortality in those who develop respiratory complications and require admission to intensive care. Extracorporeal membrane oxygenation (ECMO) is a supportive therapy option for selected severely ill patients who deteriorate despite the best supportive care. During the coronavirus disease 2019 pandemic, extra demand led to staff reorganization; hence, cardiac surgery consultants joined the ECMO retrieval team. This article describes how we increased service provisions to adapt to the changes in activity and staffing. METHODS: The data were collected from 16 March 2020 to 8 May 2020. The patients were referred through a dedicated Web-based referral portal to cope with increasing demand. The retrieval team attended the referring hospital, reviewed the patients and made the final decision to proceed with ECMO. RESULTS: We reported 41 ECMO retrieval runs during this study period. Apart from staffing changes, other retrieval protocols were maintained. The preferred cannulation method for veno-venous ECMO was drainage via the femoral vein and return to the right internal jugular vein. There were no complications reported during cannulation or transport. CONCLUSIONS: Staff reorganization in a crisis is of paramount importance. For those with precise transferrable skills, experience can be gained quickly with appropriate supervision. Therefore, the team members were selected based on skill mix rather than on roles that are more traditional. We have demonstrated that an ECMO retrieval service can be reorganized swiftly and successfully to cope with the sudden increase in demand by spending cardiac surgeons services to supplement the anaesthetic-intensivist roles. Abstract : Coronavirus disease 2019 (COVID-19) is a new contagious disease, a public health emergency and a pandemic.